Impact of Incremental Zinc Sulphate Monohydrate on Productive Performance, Blood Chemistry and Egg Quality Dynamics of Bovan Black Strain - Osayande, Unity Daniel; Iwenekha, Matthew; Jimoh, Olatunji Abubakar; Akangbe, Esther Eghosa; Unukevwere, Jerome Unuavwogbikuomawho; Obajuluwa, Olusola Victor (The Indian Journal of Animal Sciences, 2026)
This study evaluated the effect of zinc sulphate monohydrate on performance characteristics and blood chemistry of laying birds. A total of 100 Point of Lay (PoL) Bovan Black hens were randomly assigned to four dietary treatments: control (T1, 0mg/kg zinc), and treatments T2 (30mg/kg), T3 (60mg/MT), and T4 (90mg/kg). Birds were allowed access to feed and water ad libitum for 12 weeks. Parameters assessed included: feed proximate composition (%), Hen-Day Production (HDP), feed intake, egg weight, feed efficiency, percentage mortality, and blood biochemical indices. Dry matter ranged from 85.07% (T1) to 82.39% (T4), as crude protein slightly increased from 16.68.58% (T1) to 16.94% (T4). While zinc levels peaked in T4 (22.59 mg/kg), calcium (1.17%) and phosphorus (0.64–0.65%) remained constant across treatments. HDP was significantly (p<0.05) higher in T3 (70.13%) than T4 (62.52%) as Feed efficiency improved in T2 (3.17%). Total Antioxidant Capacity was significantly higher (p<0.05) in T2 (14.34 mM) than T1 (7.37 mM), as T3 (9.79 mM) and T4 (11.72 mM) showed intermediate values. Glutathione peroxidase activity was also significantly higher (p<0.05) in T2 (36.01 U/L) compared to T1 (25.13 U/L), T3 (28.88 U/L), and T4 (24.38 U/L), percentage mortality and egg quality were unaffected. Moderate zinc supplementation (30-60mg/kg) enhanced laying performance and oxidative status without adverse effects. Therefore, incorporation of zinc in laying hen’s diets enhances growth performance, improved egg quality parameters, and positively influenced health indicators and antioxidant status, highlighting its potential role in optimizing poultry nutrition and enhancing health management practices.